China Economic Update, July 2020 : Leaning Forward - COVID-19 and China's Reform Agenda - World Bank (World Bank, Washington, DC, 2020)
Economic conditions in China have changed dramatically over the past six months. The COVID-19 pandemic and measures taken to contain it have triggered a combined demand and supply shock. The report projects that economic growth in China will slow sharply to 1.6 percent this year–marking the slowest expansion since 1976–before rebounding to 7.9 percent in 2021. Even as economic activity rebounds, the pace of China’s poverty reduction is expected to slow, reflecting slower growth in household incomes. Without additional policy measures, 8-20 million fewer people are projected to escape poverty in 2020, compared to pre-pandemic projections. While risks to China’s economic outlook are exceptionally high, they can be partially mitigated by a forward-looking recovery strategy supported by good policies. The recovery offers an opportunity to accelerate China’s progress in rebalancing its economy toward more inclusive, sustainable, and greener growth.